1999
DOI: 10.1007/s002510050656
|View full text |Cite
|
Sign up to set email alerts
|

MIC-A allele profiles and HLA class I associations in Behçet's disease

Abstract: Recently a new family of non-classical MHC molecules, the MHC class I chain-related protein (MIC), encoded by genes located in the major histocompatability complex have been identified. On the basis of the location of MIC genes and the structure and expression of MIC molecules it has been postulated that MIC may be a susceptibility factor in Behçet's disease (BD). We investigated the association of the 16 described external domain alleles and the transmembrane triplet repeats of MIC-A with BD in a Middle Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 13 publications
1
50
0
2
Order By: Relevance
“…This result is consistent with previous studies associating BD and MICA*009 in Japanese, Jordanian, Palestinian, and Caucasian populations. [32][33][34] However, Marin In fact, we found in this study, as has been found in many previous studies, that HLA-B*51 was strongly associated with BD.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This result is consistent with previous studies associating BD and MICA*009 in Japanese, Jordanian, Palestinian, and Caucasian populations. [32][33][34] However, Marin In fact, we found in this study, as has been found in many previous studies, that HLA-B*51 was strongly associated with BD.…”
Section: Discussionsupporting
confidence: 71%
“…28,29 We have identifi ed a strong association between MICA*009, a genetic polymorphism in the extracellular domains of MICA (α1, exon 2; α2, exon 3; and α3, exon 4), 30,31 and BD. [32][33][34] Therefore, MICA as well as HLA-B may be a pathogenic gene of BD.…”
mentioning
confidence: 98%
“…This was supported by analysis of MICA*009 in Middle Eastern patients where the allele was in linkage with both HLA-B*51 and HLA-B*52, which only differ by two amino acids, yet only the B*51/MICA*009 combination was found in patients with BD. By comparison, B*52/MICA*009 was found in 25% of controls (8). Recently genome-wide association studies (GWASs) in different patient populations showed specific genes linked to BD in different ethnic groups; however, all the studies identified the HLA-B loci as the strongest association (9)(10)(11).…”
mentioning
confidence: 99%
“…However, it was later found that the interaction between MICA molecules and cd T cells is not restricted by the MICA gene polymorphism and does not require antigen presentation [57]. Subsequent studies in different ethnic groups have shown that the association between the MICA polymorphism and BD is secondary to strong linkage disequilibrium with HLA-B*51 [14,[58][59][60][61]. Despite the lack of a proven genetic association between MICA and BD, the autoreactive CD8?…”
Section: Mica Genementioning
confidence: 98%